Green chemistry for surface coatings, inks and adhesives : sustainable applications - Höfer, Rainer; Matharu, A. S.; Zhang, Zhanrong (Royal Society of Chemistry, 2019)
Ideal for students, researchers and industrialists working in green sustainable chemistry, industrial coatings, adhesives, inks and printing technologies.
Keywords: Green chemistry.; Surface chemistry.; elektronické knihy; electronic books